1988
DOI: 10.1099/0022-1317-69-6-1351
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Coat Protein Gene of Tomato Golden Mosaic Virus

Abstract: SUMMARYAn open reading frame, designated AR1, on DNA component A of tomato golden mosaic virus has been identified as the virus coat protein gene on the basis of the molecular weight and amino acid composition of the virus capsid polypeptide, the mass spectra and N-terminal sequences of peptides produced by cyanogen bromide cleavage of the capsid polypeptide and by the binding of antibodies, induced by immunization of a rabbit with a fl-galactosidase-AR1 fusion protein, to the capsid polypeptide in a Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…The DNA A genome contains four major genes encoding coat protein (CP), replication initiator protein (Rep), transcriptional transactivator protein and replication enhancer protein [11,31,32]. The DNA B contains two genes encoding proteins required for movement of virus, host range and pathogenicity [10,28].…”
Section: Introductionmentioning
confidence: 99%
“…The DNA A genome contains four major genes encoding coat protein (CP), replication initiator protein (Rep), transcriptional transactivator protein and replication enhancer protein [11,31,32]. The DNA B contains two genes encoding proteins required for movement of virus, host range and pathogenicity [10,28].…”
Section: Introductionmentioning
confidence: 99%
“…The virus coat protein genes of ACMV and TGMV have been identified as virus-sense ORFs (AV1 and AR1) on DNA A Kallender et al, 1988). Mutational analyses have shown that a functional coat protein is not required for systemic spread or symptom development of either virus (Gardiner et al, 1988;Morris et al, 1988;.…”
Section: Introductionmentioning
confidence: 99%
“…Vira1 ORFs are defined according to genome component (A versus 6) and orientation relative to the common region (Hamilton et al, 1984). Rightward transcription spans ORF AR1, which encodes the 28.7-kD viral capsid protein (Kallender et al, 1988). Leftward transcription spans ORFs ALI (40.3 kD), AL2 ' Current address: Department of Botany and Microbiology, Auburn University, Auburn, AL 36849.…”
Section: Introductionmentioning
confidence: 99%